Pregnancy in a diagnosed case of cauda equina syndrome and it’s management: a case report - Pandey, Yashaswi; Saidhandhapani, Kalyani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
As with many rare conditions, little is known about cauda equina syndrome (CES) and reproduction. Knowledge pertaining to complications during pregnancy and its management in a patient with diagnosed case of CES is even more scant. The information which we have is from attending on individual cases who presented with CES diagnosed during pregnancy. The following case report demonstrates pregnancy in a known case of CES, diagnosed after sustaining a burst fracture of lumbar vertebrae followed by surgical decompression at puberty. Patient conceived spontaneously with residual disease as symptoms of perineal numbness, sensory deficit in both lower limbs and persistent saddle hypoesthesia along with foot drop and gait abnormalities and presented at 30 weeks of gestation. CES is an unusual entity that appears in between 2-6% of all cases of disc herniation in the lumbar segment. Related post-traumatic presentations are extremely rare. Pregnancy exacerbates most problems associated with spinal cord injury. Autonomic dysreflexia may present as a complication in a case of pregnancy with CES which may be life threatening and requires immediate treatment. Antenatal management and complications of pregnancy in a diagnosed case of CES has not been documented till date.